Agronomy Field Information Management System (AgroFIMS) - CGIAR Platform for Big Data in Agriculture (2018)
AgroFIMS has been tested by potential users from several CGIAR Centers and partners through two user workshops. Feedback has been very positive, and work is ongoing with KDDart Technologies to enable digital data collection using AgroFIMS templates. A field testing version of AgroFIMS-KDSmart will be available in summer 2019.